2014
DOI: 10.1097/01.aoa.0000455608.69521.dd
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Planned Cesarean or Vaginal Delivery for Twin Pregnancy

Abstract: BACKGROUND-Twin birth is associated with a higher risk of adverse perinatal outcomes than singleton birth. It is unclear whether planned cesarean section results in a lower risk of adverse outcomes than planned vaginal delivery in twin pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
168
4
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(182 citation statements)
references
References 3 publications
6
168
4
3
Order By: Relevance
“…This difference is most probably caused by the exclusion of parous women from our study. However, in the Twin Birth Study that included parous women, 30% of women who had a planned vaginal delivery and commenced this mode of delivery underwent an emergency Cesarean section. If we had included parous women in our cohort, the emergency Cesarean rate would have been 25% (158/634), which is comparable with data from the other studies.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…This difference is most probably caused by the exclusion of parous women from our study. However, in the Twin Birth Study that included parous women, 30% of women who had a planned vaginal delivery and commenced this mode of delivery underwent an emergency Cesarean section. If we had included parous women in our cohort, the emergency Cesarean rate would have been 25% (158/634), which is comparable with data from the other studies.…”
Section: Discussionsupporting
confidence: 67%
“…Compared to singletons, women with a twin pregnancy have a higher risk of both elective and emergency Cesarean delivery. However, the Twin Birth Study showed that there is no major benefit of delivering all twins by elective Cesarean section. Therefore, it is important to perform a prelabor risk assessment to identify women at high risk for Cesarean delivery who will benefit from elective Cesarean delivery and, on the other hand, women at low risk for Cesarean delivery, who can safely attempt vaginal delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for the increased rate of cesarean deliveries in twins is unclear, but appears to be due, in part, to a perception that vaginal delivery increases the risk of adverse outcomes, particularly for the after‐coming twin. The Twin Birth study , demonstrated that planned cesarean section was not superior to planned vaginal delivery with regards to maternal risk or neonatal mortality or morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…In this unique international effort to find evidence for the optimal mode of delivery for twins, planned Caesarean section did not reduce the risk for perinatal death or serious neonatal morbidity as compared to vaginal delivery . As pointed out by the authors, this finding may in part be explained by the high rate of Caesarean section (>40) in the planned‐vaginal‐delivery group, with most of these deliveries occurring during labour.…”
mentioning
confidence: 85%